2015
DOI: 10.4236/wjet.2015.33c040
|View full text |Cite
|
Sign up to set email alerts
|

The Research Progress of Endogenous Formaldehyde in Aquatic Products

Abstract: Endogenous formaldehyde in aquatic products is a hot research topic, as it is an urgent problem to be solved. This paper summarized the advance in background concentration, generation mechanism and detection methods of endogenous formaldehyde in aquatic products, and the work in the future was prospected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Spectrophotometry and high performance liquid chromatography (HPLC) are quantitative methods for formaldehyde determination. The spectrophotometric method using Nash's reagent and trichloroacetic acid (TCA) based extraction is considered a reliable, convenient, fast and safe procedure for quantitative estimation of formaldehyde in fish (Benjakul et al 2006;Zhang et al 2015). Jaman et al (2015) conducted quantitative tests of formaldehyde presence in Indian major carp rui, tilapia, Thai climbing perch, Ganges river sprat, bombay duck and ribbon fish in Mymensingh using spectrophotometry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spectrophotometry and high performance liquid chromatography (HPLC) are quantitative methods for formaldehyde determination. The spectrophotometric method using Nash's reagent and trichloroacetic acid (TCA) based extraction is considered a reliable, convenient, fast and safe procedure for quantitative estimation of formaldehyde in fish (Benjakul et al 2006;Zhang et al 2015). Jaman et al (2015) conducted quantitative tests of formaldehyde presence in Indian major carp rui, tilapia, Thai climbing perch, Ganges river sprat, bombay duck and ribbon fish in Mymensingh using spectrophotometry.…”
Section: Introductionmentioning
confidence: 99%
“…Fish and fishery products can contain high levels of formaldehyde from artificially added and endogenous sources where the foremost source is endogenous (Zhang et al 2015). Formaldehyde can be produced naturally in fish by the degradation of trimethylamine oxide (TMAO) in presence of enzyme trimethylamine oxide demethylase (TMAOase), which catalyzes the conversion of TMAO into dimethylamine and methanal (also known as formalin) (Bianchi et al 2007;Stanley and Hultin, 1984;Yeh et al 2013;Zhang et al 2015). The naturally high levels of formaldehyde in fish complicate the accurate detection of illegally added formaldehyde (Wahed et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…But, during frozen storage leaching, drip loss, denaturation, and degradation of protein and other biochemical components caused lower food value (Benjakul et al 2003, Emire andGebremariam 2010). Also, the duration of frozen storage has a great impact to increase muscle FA content to a great extent (Sotelo et al 1995, Bianchi et al 2007, Zhang et al 2015. Allow dose of FA can cause pain, vomiting, lethargy whereas a large doses a source of death for consumers (Zhang et al 2015).…”
Section: Tmaoase Tmao Dimethylamine and Formaldehydementioning
confidence: 99%
“…The supply of quality foods mainly interrupted by the different types of physical, chemical, and biological hazards present in food (Erondu and Anyanwu 2005, Bianchi et al 2007, Ahmed et al 2012, Chiou et al 2015, Handford et al 2016. Among the different chemical contaminants in food, great attention has been paid towards volatile toxic aldehydes like formaldehyde (FA) (Bianchi et al 2007;Norliana et al 2009, Zhang et al 2015. In fish, FA could be accumulated naturally upon postmortem changes and during frozen storage from the enzymatic reduction of trimethylamine-Noxide (TMAO) to dimethylamine and FA (Sotelo 1995, Bianchi et al 2007 as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) has set up a maximum daily reference dose (RfD) of 0.15 mg/kg body weight per day for formaldehyde [ 12 ] and the United States Environmental Protection Agency (USEPA) also set RfD of 0.2 mg/kg body weight per day for formaldehyde [ 4 , 13 ]. Also, the Malaysian Food and Regulation have set an FA threshold limit in fish and its products to be 5 mg/kg body weight per day [ 4 ].…”
Section: Introductionmentioning
confidence: 99%